Rapid, comprehensive, and affordable mycobacterial diagnosis with whole-genome sequencing: a prospective study - Pankhurst, L; Fermont, J; del Ojo Elias, C; Votintseva, A; Walker, T; Cole, K; Davies, J; Gascoyne-Binzi, D; Kohl, T; Kong, C; Lemaitre, N; Niemann, S; et al. (Lancet, 2015)
Slow and cumbersome laboratory diagnostics for Mycobacterium tuberculosis complex (MTBC) risk delayed treatment and poor patient outcomes. Whole-genome sequencing (WGS) could potentially provide a rapid and comprehensive diagnostic solution. In this prospective study, we compare real-time WGS with routine MTBC diagnostic workflows.